Efficient construction of wireless personal area networks for disaster control - Yasunobu, S.; Nobuhara, H.; Kawamura, Youhei (Kaoru Hirota, 2012)
Japan and Indonesia are the earthquake occurrence countries where located in the circum-Pacific volcanic zone. Researches on disaster recovery management have been important issues for both countries. Our research proposes a Disaster Recovery Management system based on the proposed low cost short-distance wireless (ZigBee) communication network and mobile phones. If every person in the disaster area is connected to this network, then the information of the position, injured person, died person, and lost person can be identified quickly. The information is processed using our soft computing method to generate a comprehensive recovery and mitigation plan. Then, the government and the rescue team can use this recovery and mitigation plan for disaster management. Also, civilian organizations can develop own rescue projects based on the proposed networks. This can shorten time in the disaster management process therefore the number of victims can be reduced.